Urban Robotics and Automation : Critical Challenges, International Experiments and Transferable Lessons for the UK /: Critical Challenges, International Experiments and Transferable Lessons for the UK. ([2018]) - Marvin, Simon, 1963-; While, Aidan H; Kovacic, Mateja; Lockhart, Andy; Macrorie, Rachel
No abstract available